Pronunciation Anxiety And Capability To Communicate Of Grade 11 Students In UM DIGOS (Conference on English Language Teaching, 2023)
Pronunciation anxiety is one of the problems encountered by the students. They are hesitant to speak the second language because they fear mispronouncing it, affecting their communication skills. Thus, this study aimed to determine the students’ pronunciation anxiety level and its relationship to their communication ability. We used a descriptive-correlational research design in the study, which included the 161 Senior High School Grade 11 students of UMDC. Consequently, findings revealed that respondents sometimes feel anxious when pronouncing words yet are highly communicative with others. Also, results showed a significant relationship between the students’ levels of pronunciation anxiety and their capability to communicate, which indicates that the pronunciation anxiety of the students affects their ability to communicate. After thorough analysis, the researchers recommended that the school administrators may conduct a student’s self-evaluation and may implement different intervention programs. Additionally, teachers may use speaking activities to help students boost their confidence in communication. Moreover, students may encourage themselves to be calm when pronouncing words. Lastly, this study may be a reference for other researchers to explore other factors related to students’ moderate achievement in overcoming pronunciation anxiety.